THE INFLUENCE OF STORYTELLING STRATEGY AND LEARNING MOTIVATION TOWARDS THE ELEVENTH GRADE STUDENTS’ LISTENING ABILITY - Barbara Barbara; Baginda Simaibang; Artanti Puspita Sari (Universitas PGRI Palembang, 2022)
The purpose of this study was to find out whether there is an influence of storytelling that can increase student learning motivation toward Eleventh Grade Students’ Listening Ability of MAN 1 Musi Banyuasin. This study was conducted using experimental research with a factorial design. The location of the research was MAN 1 Musi Banyuasin. To get the sample of research, the researcher took one class; it was class XI MIA 4. The total was 34 students. The quantitative data used in this study was taken from the students' listening ability test. The researcher used pre-test and post-test as a method to obtain relevant data. The data was analyzed by SPSS with six steps; descriptive statistics, normality test, homogeneity test, independent sample t-test, paired sample t-test, two-way analysis of variance.